2022
DOI: 10.3389/fcimb.2022.823684
|View full text |Cite
|
Sign up to set email alerts
|

Global Threat of Carbapenem-Resistant Gram-Negative Bacteria

Abstract: Infections caused by multidrug-resistant (MDR) and extensively drug-resistant (XDR) Gram-negative bacteria (GNB), including carbapenem-resistant (CR) Enterobacterales (CRE; harboring mainly blaKPC, blaNDM, and blaOXA-48-like genes), CR- or MDR/XDR-Pseudomonas aeruginosa (production of VIM, IMP, or NDM carbapenemases combined with porin alteration), and Acinetobacter baumannii complex (producing mainly OXA-23, OXA-58-like carbapenemases), have gradually worsened and become a major challenge to public health bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 204 publications
4
93
1
1
Order By: Relevance
“…Polymyxins and carbapenems are considered last-resort antibiotics for the treatment of Gram-negative bacteria; however, owing to their misuse, the problem of antibiotic resistance is worsening, particularly in low-to middle-income countries (de Carvalho et al, 2022). A multicenter surveillance study in Taiwan found that the incidence of MDR, XDR, and CR P. aeruginosa infections in hospitalized patients increased from 25.1% to 27.5%, 7.7 to 8.4%, and 19.7% to 27.5%, respectively, between 2016 and 2018 (Jean et al, 2022). In the past decade, hospital-associated P. aeruginosa has showed high MDR/CR numbers in Europe, with prevalence rates of more than 30% (Micek et al, 2015).…”
Section: The Importance Of the Polymyxins In Non-fermentative Bacteri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymyxins and carbapenems are considered last-resort antibiotics for the treatment of Gram-negative bacteria; however, owing to their misuse, the problem of antibiotic resistance is worsening, particularly in low-to middle-income countries (de Carvalho et al, 2022). A multicenter surveillance study in Taiwan found that the incidence of MDR, XDR, and CR P. aeruginosa infections in hospitalized patients increased from 25.1% to 27.5%, 7.7 to 8.4%, and 19.7% to 27.5%, respectively, between 2016 and 2018 (Jean et al, 2022). In the past decade, hospital-associated P. aeruginosa has showed high MDR/CR numbers in Europe, with prevalence rates of more than 30% (Micek et al, 2015).…”
Section: The Importance Of the Polymyxins In Non-fermentative Bacteri...mentioning
confidence: 99%
“…In China, Acinetobacter spp. showed a high level of resistance to all carbapenems caused by plasmids carrying various carbapenemase genes (Jean et al, 2022). In a 2022 report from Europe, healthcare-associated isolates of CR-Acinetobacter spp.…”
Section: The Importance Of the Polymyxins In Non-fermentative Bacteri...mentioning
confidence: 99%
“…The increasing Carbapenem-resistant Enterobacterales (CRE) isolates are a severe threat worldwide due to the poor prognosis and limited therapeutic options. [1][2][3] The production of carbapenemases such as Klebsiella pneumoniae carbapenemase (KPC), Metallo-β-lactamases (MBLs) and oxacillinases (OXA) enzymes mainly cause carbapenem resistance. Moreover, the deficiency in the outer-membrane protein expression plays a minor role in carbapenem resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As an infectious disease specialist struggling to propel the proper use of antibiotics, I have gone through the most recent article in your esteemed journal written by Seidelman et al [1]. In this age of antimicrobial resistance [2], promoting antimicrobial stewardship is increasingly highlighted worldwide [3]. Therefore, evaluating the clinical impacts of antibiotic stewardship rounds in intensive care units (ICU) where broad-spectrum antibiotics are prescribed is vital.…”
mentioning
confidence: 99%